احالة أعضاء السلطة التشريعية في العراقي الى التقاعد(A comparative study) - اسراء عبد الزهرة سالم/ علاء نافع كطافة ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The members of the legislative authority are entrusted with public service, and therefore the amended Public Retirement Law No. 5 of 2014 applies to them when referring them to retirement. Referring members of the legislative authority to retirement signifies the conclusion of their work within the legislative authority and their transition into retirement. This process is facilitated through the issuance of a presidential decree. It is essential to highlight the significance of studying the procedures and regulations pertaining to the retirement of members of parliament, as it sheds light on the legal provisions governing their referral. When members of parliament are referred to retirement, they may be entitled to financial rights or have concerns regarding the specific decision impacting their retirement. In terms of financial rights, individuals may request adjustments to their retirement salary or even the calculation of an end-of-service gratuity if they believe they are eligible. Initially, a request should be submitted to the Unified Retirement Authority (URA), which is responsible for calculating the retirement salary. If the request is rejected, an appeal can be made to the Retired Cases Audit Committee (RCAC). If this appeal is also unsuccessful, the deputy can further challenge the decision before the Federal Cassation Court (FCC). It’s important to note that the decision of the FCC is considered final and binding, and cannot be appealed. Regarding objections to the referral decision itself, the appropriate course of action is to file an appeal with the Administrative Judiciary Court (AJC), which holds jurisdiction over administrative decisions issued by the President of the Republic. The presidential decree that refers members of parliament to retirement is considered an administrative decision. Any decision made by the AJC can be appealed before the Supreme Administrative Court, whose ruling is considered final, binding, and not subject to further appeal.